Failure Mode and Effect Analysis (FMEA) of Pneumatic System of CNC Milling Machine - Yudi Dwianda (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2021)
The purpose of this study is to determine the type of failures, the causes, as well as efforts and proposed actions that can be taken to improve the performance of the pneumatic system of CNC milling machines. The Failure Mode and Effect Analysis (FMEA) method is used to find priority problems through Risk Priority Number (RPN) for pneumatic system of components of CNC milling machine. The results of critical component analysis were a leakage occurs in pneumatic valve component, which the most critical risk of the RPN value. It potential failure was caused the high humidity and poor air quality from the compressor, which the RPN of 392 and 384 respectively. The proposed improvement was the replacement of damaged components and optimizing the preventive maintenance, which follow the right operation and maintenance procedures recommended as suggested by the manufacturer.